2021
DOI: 10.1021/acs.jafc.1c00284
|View full text |Cite|
|
Sign up to set email alerts
|

Cedrol from Ginger Ameliorates Rheumatoid Arthritis via Reducing Inflammation and Selectively Inhibiting JAK3 Phosphorylation

Abstract: Ginger, as a food spice, is widely applied due to its extensive effects. Cedrol (CE) found in ginger is a sesquiterpene with anti-inflammatory activity. The objective of this research is to discuss the efficacy of CE on ameliorating rheumatoid arthritis (RA). CE inhibited chronic inflammation and pain in a dose-dependent manner accompanied by rapid onset and long duration. Besides, CE treatment effectively ameliorated the paw edema volume and arthritis score with no significant effect on body weight. Organ ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 64 publications
(104 reference statements)
0
11
0
Order By: Relevance
“…Cedrol, which can be found in ginger, was also considered able to attenuate inflammation in RA. It was verified by animal models that cedrol could inhibit the phosphorylation of JAK3 protein, thus inhibiting the secretion of pro-inflammatory cytokines, and decreasing the neutrophil count (75).…”
Section: Nutrients Ameliorate Inflammationmentioning
confidence: 93%
“…Cedrol, which can be found in ginger, was also considered able to attenuate inflammation in RA. It was verified by animal models that cedrol could inhibit the phosphorylation of JAK3 protein, thus inhibiting the secretion of pro-inflammatory cytokines, and decreasing the neutrophil count (75).…”
Section: Nutrients Ameliorate Inflammationmentioning
confidence: 93%
“…We next examined the application of stereoediting as a late-stage diversification strategy. Cedrol is an important fragrance compound, and molecules that contain the cedrane scaffold have shown activity in diverse biological settings ( 30 , 31 ). Studies of structurally related C-7 cedrane epimers have not yet been reported.…”
Section: Tools For Late-stage Diversification and To Expand The Chira...mentioning
confidence: 99%
“…Cedrol has been reported to exhibit a number of biological activities, including anticancer [92][93][94] and anti-inflammatory. For example, cedrol was shown to have analgesic and anti-inflammatory effects in complete Freund's adjuvant (CFA)-induced arthritis in rats [95] and in mice with collagen-induced arthritis (CIA) [96]. This sesquiterpene also attenuated neuropathic pain in chronic constriction injury of rats by inhibiting the inflammatory response [97].…”
Section: Identification Of Potential Protein Targets For Cedrolmentioning
confidence: 99%